Host Response Protein Biomarkers Indicative of Persistent Acute Kidney Injury in Critically Ill COVID-19 Patients - Thei S. Steenvoorden, MD; Koen C. de Kruijf, BSc; Brent Appelman, MD; Bas Moggre, MD; Lieuwe D. J. Bos, MD, PhD; Alexander P. J. Vlaar, MD, PhD; Reneé A. Douma, MD, PhD; Fabrice Uhel, MD, PhD; Jesper Kers, MD, PhD; Jetta J. Oppelaar, MD; Lonneke A. van Vught, MD, PhD; Martijn Beudel, MD, PhD; et al. (Critical Care Explorations)
IMPORTANCE:. Sepsis-related host-response anomalies contribute to acute kidney injury (AKI) duration. Data on the host-response specific to COVID-19-associated AKI (COVID-AKI) in critically ill patients is limited. OBJECTIVES:. We postulated that persistent COVID-AKI (> 48 hr) differs in host response from transient (< 48 hr) or no COVID-AKI. DESIGN, SETTING, AND PARTICIPANTS:. This prospective biomarker study observed patients with severe acute respiratory syndrome coronavirus 2 infection, without chronic kidney disease, in three ICUs from March 2020 to July 2020. AKI was assessed by hourly urine output and daily plasma creatinine. MAIN OUTCOMES AND MEASURES:. Luminex and enzyme-linked immunosorbent assay were used to analyze 48 plasma protein biomarkers across six pathophysiological domains, which were tested with mixed-effects models. RESULTS:. Of 177 included patients, 106 (59.9%) had AKI within the first 48 hours of admission, of whom 76 (71.7%) had persistent AKI and 30 (28.3%) transient AKI. Those with persistent AKI often had obesity, hypertension, and a higher Sequential Organ Failure Assessment score due to the renal component. Longitudinal analyses revealed that seven proteins were elevated in persistent AKI compared with no AKI. These were related to inflammation (triggering receptor expressed on myeloid cells 1, p < 0.001; tumor necrosis factor receptor 1, p < 0.001; procalcitonin, p = 0.001), complement activation (mannan-binding lectin serine protease-2, p = 0.001), kidney dysfunction (cystatin C, p < 0.001; neutrophil gelatinase-associated lipocalin, p < 0.001), and lung dysfunction (Clara cell secretory protein 16, p < 0.001). AKI (duration) was not associated with differences in the cytokine signaling, endothelial cell activation, or coagulation domains. CONCLUSIONS AND RELEVANCE:. In contrast with sepsis-associated AKI, primarily inflammation-related biomarker levels correlated with COVID-AKI persistence. This study offers insights into COVID-AKI and may guide approaches to mitigate its persistence.